2012
DOI: 10.1177/147323001204000136
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Thyroid Nodule Calcification Morphology on Ultrasound and Thyroid Carcinoma

Abstract: Thyroid microcalcifications are strongly associated with thyroid carcinoma, especially micropapillary carcinoma. When cervical lymph node calcification is present, immediate surgery is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
(24 reference statements)
3
37
0
Order By: Relevance
“…Of these, 235 studies were retrieved for further investigation, and 41 studies (14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54) met the final selection criteria and were included in the analysis. All 41 studies were observational studies published in peer-reviewed journals between 1989 and 2012.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Of these, 235 studies were retrieved for further investigation, and 41 studies (14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54) met the final selection criteria and were included in the analysis. All 41 studies were observational studies published in peer-reviewed journals between 1989 and 2012.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…However, the reported sensitivity and specificity values in our study correlate with those reported in the literature, with microcalcifications and irregu lar margins representing the most sensitive and specific tests available for stratifying malignant risk. [23][24][25][26] The TI-RADS scoring criteria were developed to help address the challenge of stratifying the risk of malignancy in thyroid nodules, which are prevalent in up to 60% of the general population. 3,12,13 The most recent studies examining TI-RADS, both prospectively and retrospectively, allow for a clear distinction between malignant and benign nodules in the vast majority of cases when all scoring criteria are applied.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,25,27,28 The proper application of this system would benefit most from the use of standardized synoptic reporting tools that have been embraced by the surgical community as well as pathologists. In varied settings, including thyroid cancer and pancreatic cancer, synoptic reporting has been examined by international studies and validated as a method for capturing clinical data and improving patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many sonological features like irregular margins, micro calcifications, taller than wider shape, marked hypoechogenicity have been shown to have predilection for malignancy. [1][2][3][4][5][6][7] However, there is also overlap in the appearance of benign and malignant t hyroid nodules. Due to inconsistent predictive value of USG features, fine needle aspiration and cytopathological…”
Section: Introductionmentioning
confidence: 99%